Assessment and interpretation of internal doses: uncertainty and variability. (June 2016) - Paquet, F.; Bailey, M.R.; Leggett, R.W.; Harrison, J.D.
Internal doses are calculated on the basis of knowledge of intakes and/or measurements of activity in bioassay samples, typically using reference biokinetic and dosimetric models recommended by the International Commission on Radiological Protection (ICRP). These models describe the behaviour of the radionuclides after ingestion, inhalation, and absorption to the blood, and the absorption of the energy resulting from their nuclear transformations. They are intended to be used mainly for the purpose of radiological protection: that is, optimisation and demonstration of compliance with dose limits. These models and parameter values are fixed by convention and are not subject to uncertainty. Over the past few years, ICRP has devoted a considerable amount of effort to the revision and improvement of models to make them more physiologically realistic. ICRP models are now sufficiently sophisticated for calculating organ and tissue absorbed doses for scientific purposes, and in many other areas, including toxicology, pharmacology and medicine. In these specific cases, uncertainties in parameters and variability between individuals need to be taken into account.